Safe standard remnant liver volume after hepatectomy in HCC patients in different stages of hepatic fibrosis - Zhiming Zhang; Gaoxiong Ouyang; Peng Wang; Yuan Ren; Yukai Liu; Jun Chen; Yumei Zhang; Jianyong Liu; Lequn Li (BMC Surgery, 2021)
Abstract Background To determine the standard remnant liver volume (SRLV) threshold to avoid postoperative hepatic insufficiency inpatients in different stages of hepatic fibrosis who undergo right hemi-hepatectomy. Methods Data for 85 patients at our single medical center were analysed prospectively to examine whether the following factors differed significantly between those who experienced postoperative hepatic insufficiency and those who did not: height, prothrombin time, remnant liver volume, SRLV or hepatic fibrosis stage. Results Logistic regression showed SRLV and hepatic fibrosis stage to be independent risk factors for postoperative hepatic insufficiency. The threshold SRLV for predicting insufficiency was 203.2 ml/m2 across all patients [area under receiver operating characteristic curve (AUC) 0.778, sensitivity 66.67%, specificity 83.64%, p<0.0001), 193.8 ml/m2 for patients with severe hepatic fibrosis (AUC 0.938, sensitivity 91.30%, specificity 85.71%, p<0.0001), and 224.3 ml/m2 for patients with cirrhosis (AUC 0.888, sensitivity 100%, specificity 64.29%, p<0.0001). Conclusions Right hemi-hepatectomy may be safer in Chinese patients when the standard remnant liver volume is more than 203.2 ml/m2 in the absence of hepatic fibrosis or cirrhosis, 193.8 ml/m2 in the presence of severe hepatic fibrosis or 224.3 ml/m2 in the presence of cirrhosis.